2020
DOI: 10.1111/appy.12392
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic activity as a potential biomarker of negative symptoms in patients with schizophrenia

Abstract: IntroductionAutonomic dysfunction in patients with schizophrenia has raised concern considering the higher cardiovascular mortality and morbidity rate. This phenomenon has been demonstrated using various measurements and is inferred to be associated with demographics, medical treatment, and psychopathology. However, few have targeted the role of negative symptoms within schizophrenia.MethodsSchizophrenia patients with stationary psychopathology were recruited from a chronic ward, a daycare center, and a nonint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…In some cases, an inverse relationship has been found with the negative symptoms (Chung et al, 2013;Huang et al, 2020;Quintana et al, 2016) and others have noted no relationship at all (Benjamin et al, 2021). The present study also identified an inverse relationship (i.e., negative symptoms were positively correlated with heart function and negatively correlated with heart 50 structure) suggesting that increased social withdrawal related to increased left ventricular functioning and structure, as well as lower heart rate and diastolic blood pressure.…”
Section: Anterior Cingulate Cortexsupporting
confidence: 58%
“…In some cases, an inverse relationship has been found with the negative symptoms (Chung et al, 2013;Huang et al, 2020;Quintana et al, 2016) and others have noted no relationship at all (Benjamin et al, 2021). The present study also identified an inverse relationship (i.e., negative symptoms were positively correlated with heart function and negatively correlated with heart 50 structure) suggesting that increased social withdrawal related to increased left ventricular functioning and structure, as well as lower heart rate and diastolic blood pressure.…”
Section: Anterior Cingulate Cortexsupporting
confidence: 58%
“…The negative symptom domain of PANSS, which largely focuses on distortions in emotional, social, and thinking processes, has been inversely related to HRV parameters in groups of patients with schizophrenia ( 28 , 31 , 34 ). Our study confirms this relation in long term monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Besides an increase in the variance of HRV was related to an increase in negative psychopathology. The negative symptom domain of PANSS, which largely focuses on distortions in emotional, social and thinking processes, has been inversely related to HRV parameters in groups of patients with schizophrenia 23,27,31 . Our study con rms this relation within each patient in long term monitoring.…”
Section: Discussionmentioning
confidence: 99%